2012
DOI: 10.1039/c1cp21827a
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and control of catalytic surface reactions with shaped femtosecond laser pulses

Abstract: We report on femtosecond laser-induced catalytic reactions of carbon monoxide and hydrogen on single crystal surfaces under high vacuum conditions. Several product molecules are synthesized, among them also species for whose formation at least three reactants are required. By applying closed-loop optimal control, we manipulate these reactions and selectively optimize the ratio of different bond-forming reaction channels, in contrast to previous quantum control experiments aiming at bond-cleavage. Further exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Successful optimal control experiments (OCEs) have included selective control of molecular vibrational [10][11][12][13][14][15][16][17] and electronic states [18][19][20][21][22][23][24][25][26][27], preservation of quantum coherence [28,29], control of photoisomerization reactions [30][31][32][33][34][35], selective manipulation of chemical bonds [36][37][38][39][40][41][42][43][44], high-harmonic generation and coherent manipulation of the resulting soft X-rays [45][46][47][48][49][50][51], and control of energy flow in biomolecular complexes [52][53][54][55]. Optimal control theory (OCT) [7,9,…”
Section: Introductionmentioning
confidence: 99%
“…Successful optimal control experiments (OCEs) have included selective control of molecular vibrational [10][11][12][13][14][15][16][17] and electronic states [18][19][20][21][22][23][24][25][26][27], preservation of quantum coherence [28,29], control of photoisomerization reactions [30][31][32][33][34][35], selective manipulation of chemical bonds [36][37][38][39][40][41][42][43][44], high-harmonic generation and coherent manipulation of the resulting soft X-rays [45][46][47][48][49][50][51], and control of energy flow in biomolecular complexes [52][53][54][55]. Optimal control theory (OCT) [7,9,…”
Section: Introductionmentioning
confidence: 99%
“…35 Recently, Gerber and co-workers have demonstrated that CO and hydrogen coadsorbed on Pd(100) produce various molecules including formaldehyde, water, etc., upon the irradiation of fs laser pulses. 36,37 In addition, they showed that the product yield ratio can be optimized by changing the time profile of excitation pulses. Definitely, we need more examples of photoinduced chemistry among adsorbates.…”
Section: B Surface Photochemistrymentioning
confidence: 99%
“…Since the advent of powerful femtosecond lasers, the field of material response to irradiation has been developing fast [1]. It is driven by a wide range of applications in materials surface and bulk processing and nanostructuring for photonics [2], catalysis [3] and biomedicine [4]. Elemental metals and alloys are a class of materials that is widely used in the ultrafast community for its relative simplicity and versatile functionality [5][6][7].…”
Section: Introductionmentioning
confidence: 99%